2015
DOI: 10.1117/1.jbo.20.10.106001
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral tissue characterization for intestinal anastomosis optimization

Abstract: Abstract. Intestinal anastomosis is a surgical procedure that restores bowel continuity after surgical resection to treat intestinal malignancy, inflammation, or obstruction. Despite the routine nature of intestinal anastomosis procedures, the rate of complications is high. Standard visual inspection cannot distinguish the tissue subsurface and small changes in spectral characteristics of the tissue, so existing tissue anastomosis techniques that rely on human vision to guide suturing could lead to problems su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Assessing dynamic changes in tissue perfusion and oxygenation aids patient management in various clinical settings and several studies have already demonstrated its potential for guiding surgical procedures. The Dallas group developed HSI technologies to quantify tissue oxygenation in renal surgery whilst others have applied the technology to guide flap reconstruction and assess vessel and bowel anastomoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing dynamic changes in tissue perfusion and oxygenation aids patient management in various clinical settings and several studies have already demonstrated its potential for guiding surgical procedures. The Dallas group developed HSI technologies to quantify tissue oxygenation in renal surgery whilst others have applied the technology to guide flap reconstruction and assess vessel and bowel anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in future work, it would be helpful to compare the viability of skin flaps performed with and without the intraoperative use of HSI‐data. Following on from existing pre‐clinical work , it will also be exciting to see whether HSI‐generated tissue oxygenation maps of vessel and bowel anastomoses may be acquired in human patients and whether its use helps to improve surgical technique and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cooperation of Google and Johnson & Johnson aims to use cellular-guided imaging in their robot [46,47]. Shademan et al [69,70] have described in vivo supervised autonomous soft tissue surgery in an open surgical setting, enabled by a plenoptic 3D and near-infrared fluorescent imaging system that supports an autonomous suturing algorithm. Based on expert human surgical practices, a computer program generates a plan to complete complex surgical tasks on deformable soft tissue, such as suturing an intestinal anastomosis [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…The use of current intraoperative dyes is further complicated by the need for preparation times, costs, dose constraints, short half-cycles, allergic reactions, injection timings, and the inability to conduct multiple-use cases [42][43][44][45]. Dye-free, intraoperative visualization of critical hidden, subsurface structures in real-time obviate the above disadvantages of dye based visualization and would be ideal most surgical procedures [46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%